Fish fillet is a superior commodity for the company of PT Dharma Samudra Fishing Industry (DSFI), and having the highest production and demand. The product of fish fillet giving a big opportunity for defect level of fish fillet and it's caused from some mistakes that happen in process production. Hence, the optimalization of input process of fish fillet production is related with six sigma methods application which try to eliminate or minimize mistakes and wastes of time and money. It is ho - I I Fithri Yunindari S; Dinarwan .; Narni Farmayanti (Buletin Ekonomi Perikanan, 2006)
Fish fillet is a superior commodity for the company of PT Dharma Samudra Fishing Industry (DSFI), and having the highest production and demand. The product of fish fillet giving a big opportunity for defect level of fish fillet and it's caused from some mistakes that happen in process production. Hence, the optimalization of input process of fish fillet production is related with six sigma methods application which try to eliminate or minimize mistakes and wastes of time and money. It is hoped the result of the project will increase in profit of the company and work productivity. This research purposes to use six sigma project that able to apply for production division of fish fillet in PT SF!. It can be happened with measuring the effectiveness of production and identifying the good way of work in production that has done with six sigma perspective. The management of work procedure of PT DSFI with fish fillet commodity based on six sigma perspective is in 4,53 sigma .level for January 2005 until Juny 2006. It means that the work procedure in fish fillet production is in a hig" category or very good. The data prove this condition by low value achievement of DPMO, that is 1.227,60 DPMO. There are seventeen Critical To Quality that is achieved by DMAIC methods in fish fillet processing that influence the quality and quantity of fish fillet. Improvement is done for seventeen Critical To Quality. The improvement target is the management of work procedure of input process .production. The important consideration is that anything can exactly connect to the targets. Those target is improvement effort carried out by production division, because the mistakes generally happened with characteristic of technical and human factor in this division. Improvement process is doing continuously so that every deficiency can be identified and examined for improvement in the future .